The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.21203/rs.3.rs-2675369/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution and abundance of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) in Benin, West Africa

Abstract: Background Updated information on the distribution and abundance of Aedes aegypti and Aedes albopictus is crucial to prepare African countries like Benin for possible arbovirus outbreaks. This study aims to evaluate the geographical distribution, the abundance, and the biting behaviors of these two vectors in Benin. Methods Three sampling techniques (Human Landing Catch (HLC), Larval sampling, and Ovitrapping) were used to collect both immature and adult stages of Aedes spp in 23 communes located along the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…aegypti and Ae. albopictus) live in sympatry [13. Aedes aegypti was found throughout the country, while Aedes albopictus was only collected in the Southern part [14]. A study by Padonou et al [15] showed a strong infestation of the municipality of Abomey-calavi by Aedes aegypti.…”
Section: Introductionmentioning
confidence: 98%
“…aegypti and Ae. albopictus) live in sympatry [13. Aedes aegypti was found throughout the country, while Aedes albopictus was only collected in the Southern part [14]. A study by Padonou et al [15] showed a strong infestation of the municipality of Abomey-calavi by Aedes aegypti.…”
Section: Introductionmentioning
confidence: 98%